CONCEPT OF PRACTICAL CALCULATION OF ZAKAT - Muhammad Dimas Hidayatullah Wildan (Universitas Islam Negeri Mataram, 2019)
Today there are interesting developments in religious awareness in the layers of Muslims in Indonesia, especially in the awareness of zakat, charity, and charity. Zakat has a very strategic role in efforts to reduce poverty or economic development. In giving zakat to those who are entitled to have a number of ceremonies, both the calculated nishab and following their haul. This paper discusses the practical concept of calculating zakat. The discussion starts from the meaning of zakat both in terms of language and according to the terms and mention of zakat in the Qur’an. The second discussion is the law of zakat, zakat is worship, Zakat is included in the category of compulsory worship (such as prayer, pilgrimage, and fasting) which has been arranged based on the Qur'an and sunnah. The next discussion is the types of zakat which consist of two types namely zakat nafs (soul), also called zakat fitrah. Zakat mâl (treasure). Followed by the conditions of zakat. The third discussion is assets that must be zakat included; livestock, trade assets, company assets, agricultural products, minerals, and marine products as well as gold and silver, professional zakat, and zakat fitrah. Nisab and levels of zakat are also discussed and the calculation table.